IMPLEMENTASI STORYTELLING DALAM MENANAMKAN NILAI AGAMA DAN MORAL PADA ANAK USIA 4 -5 TAHUN DI TK NURUL KARTIKA TEGALHARJO - Fatmasari, Ita Duwi; Nurhafit Kurniawan; Wedya Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of religious and moral values ​​is the ability to behave, act, and act. In instilling religious and moral values ​​in early childhood, a method is needed. The purpose of this study was to understand the instillation of religious and moral values ​​in early childhood through storytelling activities at NURUL KARTIKA TEGALHARJO Kindergarten. This study uses qualitative research involving teachers and students. Data were analyzed qualitatively through a data reduction approach, data presentation, and conclusion drawing. The output of this study shows that instilling religious and moral values ​​in early childhood can be done through storytelling activities at NURUL KARTIKA TEGALHARJO Kindergarten using stories that instill religious and moral values ​​in early childhood.